Development of Siphonochilus aethiopicus as a treatment for colds and influenza and gas chromatographic analysis of volatiles of an insect repellent - Maharaj, Vinesh J. (University of Pretoria, 2021)
Dissertation (MSc (Chemistry))--University of Pretoria, 2020.